ANALISIS EFEKTIVITAS DAN EFISIENSI PELAKSANAAN ANGGARAN BELANJA PADA DINAS SOSIAL KOTA MATARAM - Osi Kusumawati Kusumawati; Animah Animah; Isnawati Isnawati (Universitas Muhammadiyah Jember, 2022)
The purpose of this study is to analyze the effectiveness and efficiency of the anggaran belanja shipments at the Dinas Sosial Kota Mataram Tahun 2016-2020. Deskriptif research is the focus of this investigation. Observation and documentation are used to gather data. The results of the study show that the effectiveness of the Dinas Sosial Kota Mataram in the 2016-2020 period has met the criteria for effectiveness. Efficacy levels over the course of the time show that the execution of the mission was particularly efficient in the years 2016 and 2019. There are some anggaran that can be taken into consideration when implementing a software. A modest amount of censorship can improve the performance of a well-executed software. Incorporating the findings of this study could serve as a springboard for Dinas Sosial Kota Mataram to articulate their concerns about the efficiency and effectiveness of their belanja outreach efforts.